低温等离子体降解油料中真菌毒素的 研究进展Research progress on degradation of mycotoxins in oilseeds by low temperature plasma - 王小焕1，王戬东2，张晨霞1，刘玉兰1，马宇翔1WANG Xiaohuan1, WANG Jiandong2, ZHANG Chenxia1, LIU Yulan1, MA Yuxiang1 (Zhongguo youzhi)
低温等离子体是一种温和、高效的新型非热加工方法，其在油料中真菌毒素降解方面的研究引起了人们的广泛关注。为了对油料中真菌毒素脱除技术开发提供理论参考，综述了低温等离子体对油料中真菌毒素的降解效果及降解机制，同时探讨了低温等离子体处理对油料品质的影响，并对未来发展方向和应用前景进行了展望。油料中主要污染的真菌毒素有黄曲霉毒素（AFT）、赭曲霉毒素（OT）、玉米赤霉烯酮（ZEN）、脱氧雪腐镰刀菌烯醇（DON）和伏马毒素（FB）。低温等离子体已经被视为一种有效的脱除真菌毒素的技术，但是其降解真菌毒素的机制尚未完全解析，其降解产物的安全性需进一步验证。虽然现有研究表明，低温等离子体处理对油料品质影响较小，但因为文献较少，还需进一步验证。未来应将低温等离子体技术与其他现有技术相结合，进一步提升其安全和有效脱除油料中真菌毒素的能力。 As a mild and efficient new non-thermal processing method, low temperature plasma has attracted much attention in the study of mycotoxins degradation in oilseeds. In order to provide theoretical reference for the development of mycotoxins removal technology in oilseeds, the degradation effect and degradation mechanism of low temperature plasma on mycotoxins in oilseeds were summarized, the effect of low temperature plasma treatment on the quality of oilseeds was explored, and the direction of the future development and the prospect of the application were prospected. The main mycotoxins contaminated in oilseeds are aflatoxin (AFT), ochratoxin (OT), zearalenone (ZEN), deoxynivalenol (DON) and fumonisin (FB). Low temperature plasma has been recognized as an effective technique for mycotoxins removal, but the mechanism of mycotoxins degradation has not been fully resolved, and the safety of its degradation products needs to be further verified. Although existing studies have shown that low temperature plasma treatment has a low impact on oil quality, further validation is needed because of the scarcity of literature. In the future, low temperature plasma technology should be combined with other existing technologies to further enhance its ability to safely and effectively remove mycotoxins from oilseeds.